Employing dispersion-flattened fiber for chromatic dispersion measurement - Al-Qdah, M. T.; Abdul-Rashid, H. A.; Dimyati, K.; Ali, B. M.; Khazani, M. (SPIE Digital Library, 2006)
A new technique for measuring the accumulated chromatic dispersion (CD) in single-mode fiber (SMF) is presented. The technique uses the ratio of the beating power between pump and probe signals and the beating power between probe signal and the four-wave mixing (FWM) conjugated signal. The technique is successfully demonstrated using dispersion-flattened fiber (DFF) as a phase conjugator to achieve a 20-dB relative power variation as a result of up to 1000 ps/nm accumulated CD change. (C) 2006 Society of Photo-Optical Instrumentation Engineers.